A repcepogácsa felhasználásának lehetősége a sertéstakarmányozásban - Márkus, Richárd; Tell, Imre; Tóth, Tamás; Troján, Szabolcs (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Pig- or pork meat is still keeping its leading role in meat production- and consumption -ahead of poultry - its main rival - which has made a huge development during the past decades. The pig sector has to face huge difficulties almost continuously, anyway periodi-cally - in the EU and in Hungary, as well. The EU has included pork in a category called „light market regulation product paths", hence the development of production/consumption is exposed mostly to the extremities of markets. Because of this, a strong fluctuation in buy-up prices has also been observable up to now, according to the well-known cyclicism in the pig sector, as well as a consequence of the various pig illnesses, changes in con-sumer habits, and so on. Due to the lack of market regulations, an absurd fenomena oc-cures very often, notably: parallel to the decreasing slaughter hog procurement prices -that of forage increase. Consequently, farms have to try to minimise (or being more pre-cise) to optimise costs for the sake of their sustainability, and keeping up competitiveness. Concerning the cost-structure of animal farming, no doubt that costs of forages are deter-minant, especially in case of pig farming it can reach as much as 60-70 percent of the total. Consequently, beside applying „novel" forages, increasing effectiveness of the so-called „traditional ones" is also badly needed.